Surface-enhanced Raman scattering for dopamine in Ag colloid: Adsorption mechanism and detection in the presence of interfering species - Figueiredo, Maria L.B. [UNESP]; Martin, Cibely S. [UNESP]; Furini, Leonardo N.; Rubira, Rafael J.G. [UNESP]; Batagin-Neto, Augusto [UNESP]; Alessio, Priscila [UNESP]; Constantino, Carlos J.L. [UNESP] (Elsevier, 2020)
The dopamine, an important neurotransmitter, in abnormal concentration can be associated with the appearance of some neurological diseases. Based on the necessity of dopamine control, we propose a fast and more straightforward method to dopamine detection using surface-enhanced Raman scattering (SERS). The addition of NaCl to the AgNp colloid decreases the overlap of band signals of dopamine SERS spectra. Thus, it reveals the main dopamine bands ascribed to C-O, C-OH stretching, and catechol ring breathing. The SERS detection of dopamine in solution was obtained at low concentration. Increasing dopamine concentration from 10−6 to 10−4 mol/L promotes the growth of dopamine adsorption on the AgNp surface through the catechol ring. However, the ethylamine side chain plays an important role in the dopamine adsorption on the Ag surface as well, confirmed by theoretical calculations. The specific adsorption of dopamine on the AgNp surface allowed to detect and to distinguish the dopamine in the presence of the interfering ascorbic acid and uric acid at concentrations between 10 and 100 times higher than for dopamine.
Keywords: Adsorption mechanism; Dopamine; SERS; Silver nanoparticle